Characterization of Plant Growth Promoting Rhizobacteria (PGPR) on Capcissum annum - Indah Juwita Sari; Indria Wahyuni; Rida Oktorida Khastini; Ewi Awaliyati; Andriana Susilowati; Enggar Utari; I Nyoman Pugeg Aryantha (Jurnal Biodjati, 2021)
Plant Growth Promoting Bacteria Rhizobacteria (PGPR) is one of the potential bacteria to enhance of Capsicum annuum through inhabitation the growth of pathogenic fungi. This study aimed to characterize PGPR in chili plants (Capsicum annuum). PGPR was isolated from the soil habitat of the red chili plant in Cilegon, Indonesia. Screening was then carried out with the dual culture method on Petri dishes and tested through in vivo method on the red chili plant. The selected bacteria were characterized morphologically, biochemically, and physiologically. The results revealed that there were 14 single isolates of bacteria from the roots of the red chili plants. The five single bacterial isolates, namely Azostobacter, Azospirillum, Pseudomonas, Serratia, and Beijerinckia have good potential as PGPR based on multiple culture screening by producing clear zones and positively effect the growth of chili plants.